Pegmatite productive terrains in the Variscan Granite hosts from Northern and Central Portugal - Dias, P. A. (2013)
The detection of suboutcropping pegmatite deposits in regions recognizably fertile regarding the occurrence of pegmatites depends upon the optimization of conceptual models which support the interpretation of the regional distribution of pegmatites and the structure of their assemblies. In intra-granitic context is at concern the more conventional cartographic expression of pegmatites in connection with the structuring of granitic cupolas. The establishment of occurrence situations linked to certain lithological units or structural alignments is a pathway for the delimitation of productive research areas. Some productivity situations deduced from geological mapping include: accommodation in preferred structural directions, proximity to mixing-mingling corridors, certain petrographic structuring units that reflect irregularities in terms of flow and fractionation processes, and trends of hydrothermal and supergene alteration of host granitic masses. The detection of these aspects, to regard as exploration guides, can avail itself of remote sensing, as they represent contrasting chromatic lithotypes with sufficient surface continuity.